2020
DOI: 10.3390/agronomy10030394
|View full text |Cite
|
Sign up to set email alerts
|

Crop Yield, Ferritin and Fe(II) boosted by Azospirillum brasilense (HM053) in Corn

Abstract: An increasing global population of over 4.5 billion people drives increasing demand for calories—30% of which are satisfied by grain crops, such as maize. High-density farming practices have been implemented but tend to deplete the soil of essential elements resulting in lower nutritional value, notably iron, of cultivated crops. Low iron content in staple crops can contribute over time to severe, even fatal, micronutrient deficiencies. Enhancing grain iron content using post-harvest biofortification strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…These authors found that the application of peat + B. Thuringiensis had significantly improved the growth and yield of beans. [41] Observed a highly significant increase in growth parameters and overproduction of chlorophyll a and b by maize plants treated with the biostimulant. The larger leaf area, more the plant achieves good photosynthesis, which is favourable to better growth [42] [43].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These authors found that the application of peat + B. Thuringiensis had significantly improved the growth and yield of beans. [41] Observed a highly significant increase in growth parameters and overproduction of chlorophyll a and b by maize plants treated with the biostimulant. The larger leaf area, more the plant achieves good photosynthesis, which is favourable to better growth [42] [43].…”
Section: Discussionmentioning
confidence: 98%
“…Several authors have demonstrated the efficacy of microbial biostimulants on plant yield parameters [49] [50] [51]. It was recently found by [41] that A. brasilense biostimulant HM053 significantly increased maize yield by 53% compared to the control. In our study, biostimulants improved yield parameters in a highly significant way (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Given the general role that iron availability plays in the ability of microorganisms to thrive and compete in virtually any environment, it is not surprising that iron uptake is also a crucial function for root colonization (17,55). Recently, analysis of iron content in maize treated with the PGPB A. brasilense revealed a significant increase in total iron accumulation in seeds and higher yield (56), suggesting that PGPB can contribute to the iron metabolism of the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…This strain stored at −85 • C in Mueller Hinton nutrient broth with addition of glycerol (10%) in the laboratory was isolated and identified by [28] and characterized by [7] for its PGPR profile. The ability of P. putida to grow under different temperatures (4,16,25,30,37,40,44,48, and 50 • C) was performed by the method adapted by [29] on Mueller Hinton (MH) liquid nutrient broth inoculated with 100 µL of the bacterial culture of the tested strain for 48 h under agitation. The growth of P. putida was evaluated by reading the optical density (OD) with a spectrophotometer (BioMATE 3S, Thermo scientific, Waltham, MA, USA) at the wavelength of 600 nm and the experiments were performed in three r replicates.…”
Section: Methodsmentioning
confidence: 99%
“…This rate of improvement in height is higher than the 17% obtained by [47] following the inoculation of maize under greenhouse conditions with chitosan extracted from lobsters combined with strains of Azospirillum lipoferum-P. fluorescens-P. putida. Authors in [48] observed a significant increase in crop yield of 30-50% compared to plants not inoculated with the PGPR strain Azospirillum brasilense (HM053). Various research works have focused mainly on the evaluation of rhizobacteria for their ability to induce improvements in growth and yield parameters in cereals under controlled conditions [12,47,49].…”
Section: Effects Of Combination Chitosan and P Putida On Growth Parametersmentioning
confidence: 99%